Case Report: Psoriasis Pustulosa Generalisata in A Patient with Primary Hypothyroidism - Sri Adila Nurainiwati; Prajnamita Manindhya El Farah; Isbandiyah; Jodii Arlan Kurnia (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2026)
Introduction: Psoriasis is a chronic relapsing pathological skin condition with a genetic basis. Generalized pustular psoriasis (GPP) is the most severe type with an incidence rate of 0.9%. Psoriasis can be associated with various other diseases, one of which is hypothyroidism. Case Presentation: A 47-year-old woman presented with red patches, scaling, pustules on her face spreading throughout the body accompanied by pruritus, burning sensation, and fever. The patient had a 10-year history of recurrent erythematous scaly skin lesions and a known history of primary hypothyroidism treated with levothyroxine. Management given ceftriaxone IV 2x1g, diphenhydramine IV 2x10mg, ondansetron IV 3x4mg, paracetamol IV 1g PRN, methotrexate tablet 2x2.5mg, inbion tablet 1x1, euthyrox tablet 1x100mg. Conclusion: GPP is a rare and potentially severe form of psoriasis that requires early recognition and comprehensive management. This case highlights the coexistence of GPP and primary hypothyroidism, suggesting the importance of evaluating thyroid dysfunction and other comorbidities in patients with severe psoriasis. Multidisciplinary management, systemic therapy, laboratory monitoring, and regular follow-up are essential to improve clinical outcomes and prevent complications.